BUILDING A SPIRITUAL SPACE IN THE NEW UZBEKISTAN AND ITS MECHANISMS (International Congress on Economics, Management and Business Studies, 2026)
This article provides a scholarly analysis of the establishment of a spiritual space in the New Uzbekistan and its mechanisms. The paper also highlights that the concept of the New Uzbekistan aims to renew and develop all spheres of national life, including the spiritual and educational domain of society, which is becoming a priority direction of state policy.
Keywords: New Uzbekistan, state, human spirituality, ideology, society, development, worldview, strategy, community, citizenship.